[Rubble and Houses Under Lava Rock, Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of houses and rubble under lava rock. Black and grey rock and ash cover what once was houses only visible now at a tiny, open spot to the left. A black, dirt path sits along the hills of rock, a person in black with a pink bag walking along it. Rubble sits along a white building on the right edge of the photograph. A city is visible in the background below a brown and white streaked mountain.